Epidemiology and Management of Open Fractures in a Tertiary Care Hospital in Nepal: An Observational Study - Sagar Maharjan; Arun Kumar Chaudhary; Rohit Shrestha; Pramit Ram Shrestha; Prabesh Gautam; Ashkal Basi; Manasil Malla; Shreedhar Prasad Acharya; Sushant Kumar Khadka (Journal of Nepal Medical Association)
Introduction: An open fracture is an orthopedic emergency that requires immediate resuscitation and stabilization. Understanding presentation and management patterns can help prepare in emergency settings. This retrospective descriptive cross-sectional study stated the demographic profile, management pattern, and seasonal distribution of patients presenting with open fractures. Methods: An observational cross-sectional study was conducted in a tertiary care center, Medical records of all patients with open fractures who underwent immediate orthopedic interventions between January 2021 and December 2023 were evaluated retrospectively after obtaining ethical approval from the Institutional Review Committee (Reference number: 29/24). Descriptive statistics were used to analyze data. Results: The study included a total of 133 cases of open fractures managed during the study period. Out of these, male patients were 104 (78.20%) and female patients 29 (21.80%), with a median age of 35.00 (25.00 - 42.00) years. Mode of injuries included road traffic accidents 53 (39.85%) and falls 32 (24.06%). Tibia fracture was seen in 56 (42.11%) cases, and spinal anesthesia was used in 52.63% of cases. External fixators 36 (27.07%) and intramedullary nails 29 (21.80%) were the primary surgical interventions. Conclusions: Male patients with open fractures were more in comparison to female patients. Road traffic accidents were the most common cause of injury. Gustilo IIIB fractures were the most frequent kind of injury with tibia most commonly involved. External fixator application was the most common procedure for immediate stabilization.